2005
DOI: 10.1021/jm050041b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Quindoline Derivatives as G-Quadruplex Inducing and Stabilizing Ligands and Potential Inhibitors of Telomerase

Abstract: A new series of quindoline derivatives (4a-j) were designed and synthesized to develop novel and potent telomerase inhibitors. The interaction of the G-quadruplex of human telomere DNA with these newly designed molecules was examined via circular dichroism spectroscopy and electrophoretic mobility shift assay (EMSA). The selectivity between the quindoline derivative (4a) and G-quadruplex or duplex DNA was investigated by competition dialysis. These new compounds as inhibitors of telomerase were also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 34 publications
3
123
0
Order By: Relevance
“…[15] This N-methylated quinacridine was selected because it does not interact with copper, as a result of the electronic poorness of its intracyclic nitrogen atoms and the lack of an ortho-chelating system (see the Supporting Information). As seen in Figure 1 B and C, the presence of either 360A or MMQ 16 led to an increase of the 295 (positive) and 265 nm (negative) signals, as previously reported for strong quadruplex binders. [7,13,16] These observations imply that in the presence of either ligand, the antiparallel structure is stabilized (Scheme 1 A, right).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…[15] This N-methylated quinacridine was selected because it does not interact with copper, as a result of the electronic poorness of its intracyclic nitrogen atoms and the lack of an ortho-chelating system (see the Supporting Information). As seen in Figure 1 B and C, the presence of either 360A or MMQ 16 led to an increase of the 295 (positive) and 265 nm (negative) signals, as previously reported for strong quadruplex binders. [7,13,16] These observations imply that in the presence of either ligand, the antiparallel structure is stabilized (Scheme 1 A, right).…”
supporting
confidence: 85%
“…The situation is dramatically different in the presence of MMQ 16 As demonstrated by the example of MMQ 16 (Figure 1 E), a tight-binding quadruplex ligand impeded the Cu-mediated unfolding of the 22AG quadruplex. However, 360A, which is known to have a higher affinity for the quadruplex than MMQ 16 (DT 1/2 = 21 versus 16 8C, respectively; see the Supporting Information), [4a, 15, 17] did not inhibit Cu II -mediated denaturation (Figure 1 D).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…[159,160] It is interesting that 11-subsitituted quindolines (Figure 11 d) designed and synthesized by our research group show stronger telomerase inhibitory activity than the disubstituted quindolines, with tel IC 50 values of 0.44-12.3 mm. [55,161] This can be attributed to the nitrogen atom in the pyridine ring of quindoline. Electron-donating groups such as substituted amino groups at the 11-position can enhance the basicity of the nitrogen atom in the pyridine ring, which is protonated at physiological pH, resulting in an increase in the electrostatic interaction between the quindoline derivatives and the negative electrostatic center of the G-quadruplex.…”
Section: Quindoline Analoguesmentioning
confidence: 99%
“…Our previous studies showed that SYUIQ-5, a Cryptolepine derivative, could induce and stabilize G-quadruplexes (32). Long-term exposure of cells to low concentrations of SYUIQ-5 caused senescence and telomere shortening (33).…”
Section: Introductionmentioning
confidence: 99%